A New Melanesian Rock‐Art Style: Figurative Engravings at Roche Mauprat, Arama Chiefdom, New Caledonia. Issue 3 (22nd June 2021) - Sand, Christophe; Baret, David; Bolé, Jacques; Ouetcho, André‐John; Gagne, Abraham
ABSTRACT: The paper presents the initial study of a unique rock‐art site discovered at the northern tip of the Mainland (Grande Terre) of New Caledonia. On the walls of a cliff‐face at the foot of a karst outcrop near Roche Mauprat, people have carved successive layers of geometric and figurative motifs. The fine, detailed engraving style of some human figures is unlike anything identified to date in the rock‐art of New Caledonia, where petroglyph anthropomorphic motifs are very rare. We present the main themes that have been recorded, including geometrics, groups of dancing figures and sets of traditional houses surrounded by trees. Only one European figure was identified, indicating that the main engraving period was probably pre‐contact and pre‐colonial. The paper discusses the relation of this new rock‐art style to other art forms, and especially the well‐studied Kanak engraved bamboo tradition that flourished during the second half of the nineteenth century in New Caledonia. RESUME: Cet article présente la première étude d'un site d'art pariétal découvert à la pointe nord de la Grande Terre de Nouvelle‐Calédonie. Sur les murs d'une paroi au pied d'un massif de karst près de la Roche Mauprat, ont été gravés au cours du temps des ensembles de motifs géométriques et figuratifs. Le style fin et détaillé de gravures de certaines représentations humaines ne ressemble à aucun ensemble identifié à ce jour dans l'art pariétal néo‐calédonien, où les motifs anthropomorphes sont très rares dans les pétroglyphes. Nous présentons les principaux thèmes graphiques identifiés, qui incluent des figures géométriques, des groupes de danseurs, ainsi que des habitats traditionnels entourés d'arbres. Une seule figure d'un européen a été reconnu, indiquant que la période principale de gravure est probablement pré‐contact et précoloniale. L'article compare ce nouvel art pariétal avec d'autres formes d'art et en particulier la tradition bien documentée des bambous gravés Kanak, qui s'est développée durant la deuxième moitié du XIXe siècle en Nouvelle‐Calédonie.